Corporate social responsibility, product innovation, and product line. Issue 2 (14th February 2020) - Xu, Heng
Abstract : Purpose: This paper aims to investigate a firm's incentive to innovate its basic product to be socially responsible and its decision on the product line. By constructing a competition model, the paper examines the factors that affect the firm's choice on its product line with the socially responsible innovation in the presence of altruistic consumers. Such factors include the proportion of the altruistic consumers, the firm's coordination cost with the basic and innovative products, as well as the consumer's transportation cost. Design/methodology/approach: In a model of differentiated products with the competition, the author assumes that a portion of consumers has a strong preference for the socially responsible product (e.g. altruistic consumers). A firm is able to attract altruistic consumers with a socially responsible innovation but it may incur a coordination cost when both the basic and the innovated products are manufactured and sold. In a framework of a sequential game, the firms make a decision on the prices, innovation inputs, as well as the choice on its product line to achieve the expected profit maximization. Findings: The firm has the incentive to engage in socially responsible innovation to better compete with its rivals. More importantly, the results of the paper explain why some firms wish to manufacture and sell the basic product even though the innovation is successful. The main factors that affect such a firm's decision include the proportion of the altruistic consumers, the aggregate benefit to all the consumers who purchase the innovative product, the firm's potential coordination cost and the consumer's transportation cost. Originality/value: The paper sheds light on a firm's corporate social responsibility innovation and its product line determination. The results of this paper can be widely applied in the firm's strategy of engaging in corporate social responsibility with eco-friendly elements that can attract altruistic consumers in the market. In addition, the findings of the paper can also contribute to policy formulation in terms of innovation. Such a result enables the policymakers to understand the factors that affect the firm's motivation on innovation and helps them to better guide the firms efficiently participate in the research and development activities.